AT THE ROOT OF THE ORGANIZED TRAINING OF OIL AND GAS SPECIALISTS IN EASTERN GALICIA (UP TO 120 OIL AND GAS EDUCATION IN UKRAINE) - Mandryk, Y. I.; Bilous, L. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2018)
At first, oil extraction was carried out by people of different professions, without special training. The beginning of the organized training of oil industry specialists dates back to 1885, when in the village Sloboda Rungurska there was opened the first high school in Galicia. In the same year in the village Ropyanka there was opened the first professional oil school in Europe. In 1886 in Borislav the government created the Krajova Mining School, which was reorganized into the State College of the Virgin in Boryslav in 1928. In the article the educational program of the school, the qualification level of trained specialists and their working places are researched.In addition to public schools in Galicia, they ] created a private school for training specialists in oil industry (in 1935 in Yaslo city). Than is how the organized training of specialists for oil and gas production in Eastern Galicia was developed.